2018
DOI: 10.1002/cphc.201800570
|View full text |Cite
|
Sign up to set email alerts
|

Low‐cost LED‐based Photo‐CIDNP Enables Biocompatible Hyperpolarization of 19F for NMR and MRI at 7 T and 4.7 T

Abstract: Substrates containing 19F can serve as background‐free reporter molecules for NMR and MRI. However, in vivo applications are still limited due to the lower signal‐to‐noise ratio (SNR) when compared with 1H NMR. Although hyperpolarization can increase the SNR, to date, only photo‐chemically induced dynamic nuclear polarization (photo‐CIDNP) allows for hyperpolarization without harmful metal catalysts. Photo‐CIDNP was shown to significantly enhance 19F NMR signals of 3‐fluoro‐DL‐tyrosine in aqueous solution usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
32
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(35 citation statements)
references
References 28 publications
2
32
1
Order By: Relevance
“…The first anomalous lines related to CIDNP were serendipitously observed in 1967 independently by Bargon et al (1967) and Ward and Lawler (1967). The radical pair mechanism was proposed by Kaptein and Oosterhoff (1969) and by Closs (1969) 2 years after and remains the cornerstone of the CIDNP theory ever since. Kaptein demonstrated that the polarization arises from the formation and the recombination of a radical pair in a magnetic field.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…The first anomalous lines related to CIDNP were serendipitously observed in 1967 independently by Bargon et al (1967) and Ward and Lawler (1967). The radical pair mechanism was proposed by Kaptein and Oosterhoff (1969) and by Closs (1969) 2 years after and remains the cornerstone of the CIDNP theory ever since. Kaptein demonstrated that the polarization arises from the formation and the recombination of a radical pair in a magnetic field.…”
Section: Introductionmentioning
confidence: 95%
“…Initially, our recent efforts have been to push the dye absorption towards more biocompatible wavelengths such as the near-infrared region (650-900 nm). In parallel, the performance of photo-CIDNP with a readily handled light source is a contemporary goal (Bernarding et al, 2018). These efforts yielded the discovery of the Atto Thio 12 (AT12) dye which monitored CW-photo-CIDNP experiments with a promising signal-to-noise enhancement (SNE) after laser irradiation at 450 nm (Sobol et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Several strategies were proposed to enhance 19 F-MRI sensitivity including the use of high-end cryogenic rf coils, [20] paramagnetic relaxation enhancement, [21] crystallographic defect induction, [22] compressed-sensing-based schemes [23] and even hyperpolarization techniques. [24] The 19 F-GEST approach shown here offers an alternative strategy to detect very low levels of thermally polarized pools of fluorine-19 spins with readily available hardware and can open new avenues for the development of advanced molecular architectures for the growing field of hotspot 19 F-MRI, which, so far, has not been used for mapping targets at very low concentrations. 19 F-MRI signal overlaid on the 1 H-MRI of alive mouse anesthetized with 4% G 4 .f,g) 19 F-ISIS-GEST data of two voxels acquired from the regions injected with f) H 2 :G 4 (magenta) and g) H 7 :G 4 (green).…”
Section: Discussionmentioning
confidence: 99%
“…Initially, our recent efforts have been to push the dye absorption towards more biocompatible wavelength such as near infrared (650-900 nm). In parallel, the performing of photo-CIDNP with readily handled light source is a contemporary goal (Bernarding et al, 2018). These efforts yielded to the discovery of the Atto Thio 12 (AT12) dye which monitored photo-CIDNP experiments with a promising signal-to-noise enhancement (SNE) after laser irradiation at 450 nm (Sobol et al, 2019).…”
Section: Discussion Open Accessmentioning
confidence: 99%